Aimed at Sniečkus but hit Berklavs... Twists and Turns of the Thaw Policy in Soviet Lithuania in 1958–1959 - Sirutavičius, Vladas (History / Istorija, 2024)
Abstract. De-Stalinisation not only formed prerequisites for the liberalisation of social and political life but also encouraged tensions between the “periphery” (the elites of the Soviet republics) and the “centre” (Moscow). Conflicts between the leaderships of Soviet Latvia and Azerbaijan and Moscow are better known to historiography. However, practically at the same time, tensions arose between the first secretary of the Lithuanian Communist Party, A. Sniečkus, and the leaders of the USSR. The tensions were fueled by the reform of the education system initiated by N. Khrushchev, the first secretary of the Communist Party of the Soviet Union, and a particularly new cadres policy (refusal of the principle of promoting national cadres to leadership positions in the republics.) The article discusses the course of conflicts and answers the question of how and why A. Sniečkus was successful in preventing tensions between the republic and the centre.